Layer-by-Layer Thin Film of Iron Phthalocyanine as a Simple and Fast Sensor for Polyphenol Determination in Tea Samples - Maximino, Mateus Dassie; Martin, Cibely Silva; Paulovich, Fernando Vieira; Alessio, Priscila (Wiley, 2016)
Polyphenols have attracted attention due to their antioxidant capacity and beneficial effects to health. Therefore, fast, inexpensive, and efficient methods to discriminate and to quantify polyphenols are of interest for food industry. In this paper, Layer-by-Layer films of poly(allylamine hydrochloride) and iron tetrasulfonated phthalocyanine were employed as sensor for determination of polyphenols in green tea (camellia sinensis), and green and roasted mate teas (ilex paraguariensis). The polyphenol sensor was tested in catechol standard solution by differential pulse voltammetry (DPV), reaching a limit of detection of 1.76 × 10-7 mol/L. The determination of polyphenols in the tea samples was obtained by analytical curve and catechol standard addition using electrochemical techniques. Projection techniques (information visualization) were applied to the DPV results of the tea samples and a pattern of separation following the phenolic content was obtained. The results support the application of the sensor in fast classification of beverages according to their polyphenol content.
Keywords: FeTsPc; LbL film; polyphenol sensor; tea samples